South Africa : Report on Observance of Standards and Codes(ROSC)-Data Module. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2001)
The Money and Banking Division of the Research Department of the South African Reserve Bank plans to conduct a review of its entire time series database following the implementation of new bank reporting structures in January 2001. This is a time-consuming process, and the release of a comprehensively revised time series structure, incorporating balance-sheet information with a monthly frequency, is not expected before the end of 2003. Review of the composition of 'other assets' and 'other liabilities' and to reclassify are needed.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet